Analysis of the Evolution of the Number of Biotechnology Patents in the Agribusiness Sector - Júnior, Raymundo Lázaro Vellani; Putti, Fernando Ferrari [UNESP]; Guerrero, Pedro Henrique Lupo [UNESP]; Zanetti, Willian Aparecido Leoti [UNESP]; Silva, Adriano Bortolotti da; Góes, Bruno César (FapUNIFESP (SciELO), 2022)
Agribusiness is the most prominent sector in the Brazilian economy, contributing over the last few years with about 30% of the Gross Domestic Product (GDP) and being responsible for more than 40% of the products exported by the country. During this period, several economic development programs in Brazil were created by the federal government, contemplating the agricultural sector to increase productivity in the field, with actions and intensification of the use of fertilizers, pesticides, creation of agricultural research institutes, training of agronomists, and veterinarians, in addition to facilitating access to credit for rural producers. In this sense, the biotechnology sector great significant greatly influenced the expansion of agricultural production, increasing field efficiency and agricultural production productivity. The objective of this work was to analyze the number of patents in the agribusiness sector to technological development in the biotechnology sector between 1978 and 2018, with data from the Brazilian National Institute of Industrial Property (INPI). There is a growing number of patents over the period, as well as an increase in the number of undergraduate and graduate courses in the field of biotechnology in the country since the sector is considered strategic as a source of innovation in science and technology, supporting the country’s development, structuring itself to sustain economic growth, with research, science, technology, and innovation.
Keywords: Innovation; INPI; Technology; Transgenic